2021
DOI: 10.3390/ma14020442
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Based Prediction of Joint Hardness in TIG Welding of Inconel 600, 625 and 718 Nickel Superalloys

Abstract: Welding is an important process in terms of manufacturing components for various types of machines and structures. One of the vital and still unsolved issues is determining the quality and properties welded joint in an online manner. In this paper, a technique for prediction of joint hardness based on the sequence of thermogram acquired during welding process is proposed. First, the correspondence between temperature, welding linear energy and hardness was revealed and confirmed using correlation analysis. Usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 37 publications
(36 reference statements)
1
16
0
Order By: Relevance
“…Furthermore, Ramkumar et al [ 48 ] have reported that the poor solubility of Mo in the austenitic matrix due to the large size radius results in segregation of Mo at the inter-dendritic areas as observed from Figure 12 c,g, which facilitates the formation of Mo-enriched Mo 2 C or Laves phase. The formation of the Mo- and Cr-enriched M 23 C 6 phase in the weld metal region has also been reported in previous research [ 49 , 50 , 51 ].…”
Section: Resultssupporting
confidence: 83%
“…Furthermore, Ramkumar et al [ 48 ] have reported that the poor solubility of Mo in the austenitic matrix due to the large size radius results in segregation of Mo at the inter-dendritic areas as observed from Figure 12 c,g, which facilitates the formation of Mo-enriched Mo 2 C or Laves phase. The formation of the Mo- and Cr-enriched M 23 C 6 phase in the weld metal region has also been reported in previous research [ 49 , 50 , 51 ].…”
Section: Resultssupporting
confidence: 83%
“…For this operation, a constant emissivity ε = 0.13 was used. According to previous research, the emissivity of the Inconel 625 alloy is below ε = 0.2 [18]. After additional evaluations, it was found that it is even lower.…”
Section: Methodsmentioning
confidence: 79%
“…Additionally, there is the possibility of grease patches or oxidized zones and spatter that have different (higher) emissivity levels than the base material surface. In [18] this was the case for the water glass used to protect thermocouples from high temperature. These areas are often interpreted as hot spots that are considered damaged zones.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…TIG welding was observed to be a very useful technique for stainless steels, high-carbon steels, nickel-based superalloys, etc. [3][4][5][6]. However, limited productivity of the process, particularly for single pass operations, are always a problem.…”
Section: Introductionmentioning
confidence: 99%